Rosemary Butcher Choreography, Collisions and Collaborations. Book review. - Roy, Sanjoy (Dance Books Ltd., Alton,Hampshire (UK), 2006)
PALABRAS CLAVE: Rosemary Butcher.
Edited by Rosemary Butcher & Susan Melrose Middlesex University Press, 2005.